We - Zamyatin, Yevgeny (New York Modern Library Paperback Edition, 2006)
Written in 1921, We is set in the One State, where all live for the collective good and individual freedom does not exost. The novel takes the of the diary of mathematician D-503, who to his shock, experiences the most disruptive emotion imaginable: love. At once satirical and sobering and now available in a powerful new translation We is both a rediscovered classic and a work of tremendous relevance to our times.
Keywords: Literature